A bateria no baião e no frevo: propostas de estudo a partir da performance do baterista Luizinho Duarte com o Grupo Marimbanda em quatro obras do álbum Tente Descobrir - Sousa, Magno Altieri Chaves de (2021)
This work aims to propose studies for the baião and frevo rhythms applied to the drums instrument, based on the performance of the musician Luiz Duarte do Nascimento, also known in the artistic field as Luizinho Duarte. For this, four songs were chosen and analyzed from the album Tente Descobrir (2005), recorded by the group Marimbanda. After analysis, some paths were traced from the performance of the musician, being: a brief historical trajectory of the baião and frevo rhythms until the insertion of the drums in these two musical genres. In this context, scientific works were identified in the academic field on the performance of Brazilian drummers in dialogue with the didactic materials found, which bring the baião and frevo rhythms applied to the drums. As a result of this research, from the performance elements identified in the peculiarities of execution of the baião and frevo rhythms by Luizinho Duarte, five studies are proposed for each of these musical genres applied to the drums, in addition to rhythmic patterns for the instrument.